The effect of block copolymer additives for a highly active polymeric metal-free oxygen reduction electrode. Issue 34 (21st March 2016) - Pering, Samuel R.; Nicholas, James A.; Bayatsarmadi, Bita; Evans, Drew; Fabretto, Manrico; Blencowe, Anton; Murphy, Peter J.; Talemi, Pejman
Abstract : The effect of triblock copolymer additives on polymeric ORR electrodes is studied and a highly efficient polymeric electrode is developed. Abstract : Electrocatalytic materials play a critical role in emerging clean energy technologies such as batteries and fuel cells. Herein, we report the fabrication of a unique conducting polymer alloy thin film electrocatalyst based on poly(3, 4-ethylenedioxythiophene) (PEDOT) and a polymeric additive, polyethylene glycol–polydimethylsiloxane–polyethylene glycol. These polymeric films displayed electrocatalytic activity for the Oxygen Reduction Reaction (ORR) higher than that of platinum or other polymeric electrodes. Furthermore, the metal-free polymeric electrodes were not susceptible to 'poisoning' when exposed to methanol. The fabrication parameters affecting the ORR performance of the polymeric electrodes and the mechanism of the improvement of the ORR catalysis were comprehensively investigated and benchmarked against commercial Pt electrodes. The application of the conducting polymer alloy electrode in a zinc–air battery demonstrated high power output and stable performance.